Nuptiality in Sub-Saharan Africa: Contemporary Anthropological and Demographic Perspectives - (:unkn) unknown (My University, 1994)
Two much-needed contributions to the literature in an analysis of the dynamics of marriage and partnership-formation in Africa. This is a perennially lively and interesting subject in Africa, the most complex of continents. Many of the studies are based on careful field research, making this a rich and original source of information on this diverse and rapidly changing area in a combination of anthropological theorizing with demographic case studies. By taking this approach, the authors create ways of testing the theories and of conceptualizing the data. The papers are united by their use of new methodological and analytical strategies that can link anthropology and demography. The contributors and editors argue that demographic studies need anthropological insights into culture and society to understand the marriage process, and as certain its effects on demographic events such as fertility, divorce, and child mortality. A primary theme of this volume is the fluidity of marriage and partnership-formation noticed in African societies. The contributors argue that marriage is less of a discrete event than a continuous process lasting several years, and that the ‘processual' approach taken by theoretical anthropologists (where individuals use and manipulate rules, rather than conform to fixed categories) can be very useful for studying African marriage in the light of demographic data.
Keywords: African Research